The Role of Environmental Adult Education in Community Development - Ebere P. U (PT FORMOSA CENDEKIA GLOBAL, 2022)
This paper examined the role of environmental adult education in community development. In this study, the concept of adult education, its objectives and its relevant was properly stated, it also investigates the concept of environmental adult education, its objectives and principles, the concept of community development and its objectives, and lastly the role adult education in community developmental drive. In conclusion, this study discovered that, our environment is full of activities daily by man, industries and other natural occurrences which needed to be properly managed and controlled. The role of every adult in the society should not be under-mind, which calls for mass campaign or sensitization of the need for human capacity development, development of indigenous people in our communities should be paramount in the pursuit of this environmental issues as the only solution or a way out the problems we are facing these days especially in Rivers State and other part of the country.